ERF9 of Poncirus trifoliata (L.) Raf. undergoes feedback regulation by ethylene and modulates cold tolerance via regulating a glutathione S‐transferase U17 gene. Issue 1 (29th September 2021) - Zhang, Yang; Ming, Ruhong; Khan, Madiha; Wang, Yue; Dahro, Bachar; Xiao, Wei; Li, Chunlong; Liu, Ji‐Hong
Summary: Plant ethylene‐responsive factors (ERFs) play essential roles in cold stress response, but the molecular mechanisms underlying this process remain poorly understood. In this study, we characterized PtrERF9 from trifoliate orange ( Poncirus trifoliata (L.) Raf.), a cold‐hardy plant. PtrERF9 was up‐regulated by cold in an ethylene‐dependent manner. Overexpression of PtrERF9 conferred prominently enhanced freezing tolerance, which was drastically impaired when PtrERF9 was knocked down by virus‐induced gene silencing. Global transcriptome profiling indicated that silencing of PtrERF9 resulted in substantial transcriptional reprogramming of stress‐responsive genes involved in different biological processes. PtrERF9 was further verified to directly and specifically bind with the promoters of glutathione S‐transferase U17 ( PtrGSTU17 ) and ACC synthase1 ( PtrACS1 ). Consistently, PtrERF9 ‐overexpressing plants had higher levels of PtrGSTU17 transcript and GST activity, but accumulated less ROS, whereas the silenced plants showed the opposite changes. Meanwhile, knockdown of PtrERF9 decreased PtrACS1 expression, ACS activity and ACC content. However, overexpression of PtrERF9 in lemon, a cold‐sensitive species, caused negligible alterations of ethylene biosynthesis, which was attributed to perturbed interaction between PtrERF9, along with lemon homologue ClERF9, and the promoter of lemon ACS1 gene ( ClACS1 ) due to mutation of the cis ‐acting element. Taken together, these results indicate that PtrERF9 acts downstream of ethylene signalling and functions positively in cold tolerance via modulation of ROS homeostasis by regulating PtrGSTU17 . In addition, PtrERF9 regulates ethylene biosynthesis by activating PtrACS1 gene, forming a feedback regulation loop to reinforce the transcriptional regulation of its target genes, which may contribute to the elite cold tolerance of Poncirus trifoliata .